Consumerism and Rationality Against Cultural Influence - Sirajuddin Sirajuddin; Nurmiati Nurmiati (Universitas Islam Negeri Alauddin Makassar, 2021)
The culture of consumerism has expanded globally. Basically, this ideology is a derivative of investment capitalism which gives rise to a spirit of consumption with the aim of forming